Medical Terminology for Health Professions, 8th Edition - Ann Ehrlich (Cengage Learning, 2016)
Ideal for online or classroom teaching, MEDICAL TERMINOLOGY FOR HEALTH PROFESSIONS, 8E simplifies the process of memorizing complex medical terminology by focusing on the important word parts-common prefixes, suffixes and root words-that provide a foundation for learning hundreds of medical terms. Organized by body systems, chapters follow a logical flow of information: an overview of the body system's structure and functions, a summary of applicable medical specialties, and then pathology, diagnostic, and treatment procedures. Core material for each body system is presented without interrupting exercises, enabling students to master the language necessary to describe how the body system works, what goes wrong with it, and how to treat it before putting these new skills into practice. Up-to-date illustrations reflect the latest terms and procedures, while multi-cultural/multi-generational photos accurately portray today's medical practice.